1971
DOI: 10.1104/pp.48.3.255
|View full text |Cite
|
Sign up to set email alerts
|

The Isolation and Characterization of d-Glucose 6-Phosphate Cycloaldolase (NAD-Dependent) from Acer pseudoplatanus L. Cell Cultures

Abstract: York at Buffalo, Buffalo, New York 14214 labile than the phosphatase, thus permitting the latter to be studied independently of the former (13). Chen and Charalampous (7) have achieved separation of these activities on DEAE'-cellulose using the yeast system. Partial purification of the cyclizing enzyme and related studies on cell-free systems from rat testis, yeast, and Neurospora have generated a wealth of information regarding the mechanism of action (3,8,13,16,27,31), physical and chemical properties of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…D- [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]Glucose 6-phosphate (specific activity, 60.3 mCi/mmol) and [1,[2][3] H]myo-inositol (specific activity, 370 -740 GBq/mmol) were obtained from DuPont NEN. Glucose 6-phosphate, bacterial alkaline phosphatase, and phosphate standard were purchased from Sigma.…”
Section: Methodsmentioning
confidence: 99%
“…D- [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]Glucose 6-phosphate (specific activity, 60.3 mCi/mmol) and [1,[2][3] H]myo-inositol (specific activity, 370 -740 GBq/mmol) were obtained from DuPont NEN. Glucose 6-phosphate, bacterial alkaline phosphatase, and phosphate standard were purchased from Sigma.…”
Section: Methodsmentioning
confidence: 99%
“…The rate of enzyme reaction proceeded linearly up to 90 min with G-6-P as the substrate. An earlier study with Acer pseudoplatanus showed time linearity up to 150 min with a G-6-P concentration under 4 mM (Loewus and Loewus, 1971) Effect of temperature and pH: The enzyme was highly active in the temperature range of 20-40ºC with 30ºC as the temperature maximum. Temperature maxima of 35ºC were found for the cytosolic enzymes from both higher and primitive plants (RayChoudhury et al, 1997).…”
Section: Enzyme Concentration and The Time Linearitymentioning
confidence: 99%
“…It is formed by the conversion of DGlucose-6-Phosphate (G-6-P) to L-myo-inositol-1-phosphate (I-1-P) by the enzyme L-myo-inositol-1-phosphate synthase (MIPS; EC: 5.5.1.4) and is subsequently dephosphorylated by inositol monophosphatase (EC: 3.1.3.25) to myo-inositol (Lohia et al, 1999). The MIPS reaction has been reported for archea (Chen et al, 2000), bacteria (Bachhawat and Mande, 1999;, protozoa (Lohia et al, 1999), lower plants (Donahue and Henry, 1981a;1981b;Escamilla et al, 1982;Dasgupta et al, 1984;RayChoudhury et al, 1997;Benaroya et al, 2004;Chhetri et al, 2005), higher plants (Loewus and Loewus, 1971;Loewus et al, 1978;Ogunyemi et al, 1978;Adhikari and Majumder, 1983;Johnson and Sussex, 1995;Johnson and Wang, 1996;Chun et al, 2003) and animals (Pittner and Hoffmann-Ostenhof, 1976;1979;Maeda and Eisenberg Jr., 1980;Adhikari and Majumder, 1988;Chiu et al, 2003). The present study reports the occurrences of free myo-inositol in different pteridophytes.…”
Section: Introductionmentioning
confidence: 99%
“…Generation of free myo-inositol may be blocked if MIPP is not active. The MIPS reaction has been reported to occur in a large number of living systems namely archea (Chen et al, 2000), bacteria (Bachhawat and Mande, 2000), protozoa (Lohia et al, 1999), lower plants (Donahue and Henry, 1981a,b;Escamilla et al, 1982;Dasgupta et al, 1984;RayChoudhury et al, 1997;Benaroya et al, 2004, Chhetri et al, 2005, higher plants (Loewus and Loewus, 1971;Loewus et al, 1978;Ogunyemi et al, 1978;Adhikari et al, 1987;Johnson and Sussex, 1995;Johnson and Wang, 1996;Chun et al, 2003), and animals (Pittner and Hoffmann-Ostenhof, 1976;Maeda and Eisenberg Jr., 1980;Majumder, 1983, 1988;Chiu et al, 2003). In pteridophytes, Benaroya et al (2004) and Chettri et al (2005Chettri et al ( , 2006 have recently documented the occurrence and characterization of L-myo-inositol-1-phosphate synthase.…”
Section: Introductionmentioning
confidence: 99%